Emerging therapeutic roles of exosomes in HIV-1 infection - Pang, Siew Wai *; Teow, Sin Yeang * (Academic Press, Elsevier, 2020)
Exosomes are nanometer-sized vesicles derived from endosomes of a variety of cell types and could be found in various biological fluids. The contents of exosomes vary depending on the cellular origin and state of health. Exosomes are a form of vehicle to transmit information between cells, transport wastes out of cells, and in the case of Human Immunodeficiency Virus Type 1 (HIV-1), promote infection and pathogenesis. HIV-1 and exosomes share many similarities in terms of lipid profile and protein make-up and could be the reason why the exosomal pathway is an effective route for HIV-1 to exploit. While exosomes have been shown in many instances to promote viral pathogenesis, there are also evidences that exosomes from specific cell origins could inhibit HIV-1, to a certain extent. This review summarizes the roles of exosome in promoting or inhibiting HIV-1 pathogenesis, as diagnostic biomarkers, therapeutic tools, and the challenges faced for its successful implementation in clinical applications.